Novel comparative methodology of~hybrid support vector machine with meta-heuristic algorithms to~develop an integrated candlestick technical analysis model - Armin Mahmoodi; Leila Hashemi; Amin Mahmoodi; Benyamin Mahmoodi; Milad Jasemi (Journal of Capital Markets Studies (JCMS), 2024)
Purpose The proposed model has been aimed to predict stock market signals by designing an accurate model. In this sense, the stock market is analysed by the technical analysis of Japanese Candlestick, which is combined by the following meta heuristic algorithms: support vector machine (SVM), meta-heuristic algorithms, particle swarm optimization (PSO), imperialist competition algorithm (ICA) and genetic algorithm (GA). Design/methodology/approach In addition, among the developed algorithms, the most effective one is chosen to determine probable sell and buy signals. Moreover, the authors have proposed comparative results to validate the designed model in this study with the same basic models of three articles in the past. Hence, PSO is used as a classification method to search the solution space absolutelyand with the high speed of running. In terms of the second model, SVM and ICA are examined by the time. Where the ICA is an improver for the SVM parameters. Finally, in the third model, SVM and GA are studied, where GA acts as optimizer and feature selection agent. Findings Results have been indicated that, the prediction accuracy of all new models are high for only six days, however, with respect to the confusion matrixes results, it is understood that the SVM-GA and SVM-ICA models have correctly predicted more sell signals, and the SCM-PSO model has correctly predicted more buy signals. However, SVM-ICA has shown better performance than other models considering executing the implemented models. Research limitations/implications In this study, the authors to analyze the data the long length of time between the years 2013-2021, makes the input data analysis challenging. They must be changed with respect to the conditions. Originality/value In this study, two methods have been developed in a candlestick model, they are raw based and signal-based approaches which the hit rate is determined by the percentage of correct evaluations of the stock market for a 16-day period.
Keywords: 330; Candlestick technical analysis; Machine learning; Meta-heuristic algorithms; Stock market predicting; Support vector machine